Stragtegi Pengembangan Klaster Industri Keripik Singkong Di Kabupaten Bojonegoro Menggunakan Metode K-Means Clustering dan Fuzzy AHP - Sudirman Sudirman; Lorine Tantalu (Agricultural Faculty, 2023)
Bojonegoro Regency has excellent agro-industry potential, namely cassava. These commodities can be processed into superior regional products, namely cassava chips. The center of the cassava chip industry is in the Gayam sub-district and the Kalitidu sub-district. The problems faced by the cassava chip industry in Bojonegoro Regency are currently in the raw materials, technology, product quality, business capital, marketing, and there is still no cluster division. This study aimed to determine clusters and improvement strategies in each cluster of the cassava chip industry. The method used is the K-means Clustering method and Fuzzy AHP. The study's results determined 2 clusters of cassava chips industry based on the performance of the cassava chips industry and the quality of their products. Cluster 1 consists of 3 cassava chip industries, and cluster 2 consists of 4 cassava chip industries. The strategy for developing the cassava chip industry in cluster 1 is to establish partnerships with raw materials suppliers, plant cassava on private land, and manage the handling and supply of raw materials. The development strategy for cluster 2 is to innovate products, innovate packaging designs and conduct comparative studies in other cassava chips industries.